Optimalisasi Good Governance dengan Program “SI JINGGO" dalam Sistem Pemerintahan Daeraah di Kota Probolinggo - Revanggi Ayu Tantri; Husni Mubaroq (Jurnal Studi Inovasi, 2022)
Every time people always demands quality public services from bureaucratic administrators, even though the provision of services is still not satisfying the community because often the services provided tend to be complicated or convoluted, take a long time, and the large number of fees charged so that the services provided seem impressed. inefficient and effective in service delivery. Related to the problems mentioned above, public services are an option for the strategic sector in order to realize good governance. Good Governance is all efforts in realizing a good government. Therefore, the Progobolinggo City Government made an innovation in the form of the Si Jinggo application (Good Governance Information Network Information System). Si Jinggo is an innovation in the form of a website-based program application that can be used to generate reports and data periodically from sub-districts or sub-districts throughout Probolinggo City which can be monitored online. From the Si Jinggo program, it is hoped that various problems such as those in sub-districts and urban villages are less aware that the data they provide is important for the regional development planning process, the lack of community data needed by Technical OPD such as population demographics and other community data, access to village data which is found on the website of the Ministry of Home Affairs is difficult to obtain and use by local governments, and the frequent occurrence of repeated requests for data in sub-districts and sub-districts can be resolved. With the Si Jinggo program, the Probolinggo City Government hopes to realize good governance optimally.